Metamaterials with Negative Parameters. Theory, Design, and Microwave Applications - Marques R. Ricardo (New Jersey, Wiley-Interscience, 2008)
Metamaterials with Negative Parameters represents the only unified treatment of metamaterials available in one convenient book. Devoted mainly to metamaterials that can be characterized by a negative effective permittivity and/or permeability, the book includes a wide overview of the most important topics, scientific fundamentals, and technical applications of metamaterials.Chapter coverage includes: the electrodynamics of left-handed media, synthesis of bulk metamaterials, synthesis of metamaterials in planar technology, microwave applications of metamaterial concepts, and advanced and related topics, including SRR- and CSRR-based admittance surfaces, magneto- and electro-inductive waves, and sub-diffraction imaging devices. A list of problems and references is included at the end of each chapter, and a bibliography offers a complete, up-to-date representation of the current state of the art. in metamaterials. Geared toward students and professionals alike, Metamaterials with Negative Parameters is an ideal textbook for postgraduate courses and also serves as a valuable introductory reference for scientists and RF/microwave engineers.